2010
DOI: 10.1007/s10237-010-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of bone tissue formation within a porous scaffold under dynamic compression

Abstract: A computational model of mechanoregulation is proposed to predict bone tissue formation stimulated mechanically by overall dynamical compression within a porous polymeric scaffold rendered by micro-CT. Dynamic compressions of 0.5-5% at 0.0025-0.025 s(-1) were simulated. A force-controlled dynamic compression was also performed by imposing a ramp of force from 1 to 70 N. The model predicts homogeneous mature bone tissue formation under strain levels of 0.5-1% at strain rates of 0.0025-0.005 s(-1). Under higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 35 publications
(64 reference statements)
5
45
0
6
Order By: Relevance
“…The primary function of porous biomaterial scaffolds in tissue engineering (TE) applications is to enable cells to attach, migrate and proliferate, thereby providing a suitable environment to support tissue growth (Hutmacher 2000;Kim et al 2010;Milan et al 2010). This is facilitated through the use of highly porous scaffold architectures, which enable nutrient and metabolite diffusion throughout, while also contributing to the shape and mechanical integrity of the tissue defect.…”
Section: Introductionmentioning
confidence: 99%
“…The primary function of porous biomaterial scaffolds in tissue engineering (TE) applications is to enable cells to attach, migrate and proliferate, thereby providing a suitable environment to support tissue growth (Hutmacher 2000;Kim et al 2010;Milan et al 2010). This is facilitated through the use of highly porous scaffold architectures, which enable nutrient and metabolite diffusion throughout, while also contributing to the shape and mechanical integrity of the tissue defect.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome such limitations and allow future translation of bone-engineered products, over the last years mathematical models and computer simulation techniques have been applied to an increasing extent to bioreactor systems in order to determine a priori the most favorable parameters for functional tissue regeneration from a set of available alternatives (for a review see [78]). Simulations in tissue engineering are usually divided into simulation of the biophysical environments (distribution of all physical forces) [71,79] or biological environments (including dynamics of nutrient transport, tissue growth, matrix deposition and morphological evolution) [80], or both environments [81].…”
Section: Simulation Techniques For Improved Bioreactor Designmentioning
confidence: 99%
“…Cahill et al found that models based on the designed scaffold geometry over-predicted the scaffold stiffness by up to 147% and that surface roughness is a factor that needs to be accounted for 4 . High resolution finite element meshes have been successfully generated from micro-CT scans giving accurate models of the real geometries of both bone tissue engineering scaffolds 6,10,38,49,50,52,57 and native bone tissue 2,29,40,47,51 .Micromechanics approaches to evaluate the mechanical properties of particle-reinforced composites traditionally use idealised microstructures based on particle distribution and are often modelled under periodic boundary conditions 5 . This approach was used by Eshragi et al to determine the bulk mechanical properties of a PCL/hydroxyapatite SLS scaffold 14 .…”
mentioning
confidence: 99%